Immobilization and Characterization of L-Asparaginase over Carbon Xerogels - Barros, Rita A. M. (2022)
UIDP/ 50020/2020 POCI-01-0145-FEDER-031268 no. 312463/2021-9 LA/P/0006/2020 FAPESP (2018/06908-8) CEECIND/2020/01867